P2X7 Receptor Induces Tumor Necrosis Factor-α Converting Enzyme Activation and Release to Boost TNF-α Production - Barberà-Cremades, Maria; Gómez, Ana I.; Baroja-Mazo, Alberto; Martínez-Alarcón, Laura; Martínez, Carlos M.; de Torre-Minguela, Carlos; Pelegrín, Pablo (Frontiers in Immunology, 2017)
Tumor necrosis factor (TNF)-alpha is a major pro-inflammatory cytokine produced in response to Toll-like receptor stimulation. TNF-alpha release is controlled by the activity of TNF-alpha converting enzyme (TACE) that cut membrane-bound TNF-alpha to shed its ectodomain as a soluble cytokine. The purinergic receptor P2X ligand-gated ion channel 7 (P2X7) is activated in response to elevated concentrations of extracellular ATP and induces different pro-inflammatory pathways in macrophages to establish an inflammatory response. P2X7 receptor promotes the activation of the inflammasome and the release of interleukin-1beta, the production of inflammatory lipids and the generation of reactive oxygen species. In this study, we analysed the mechanism of P2X7 receptor responsible of TNF-alpha release after priming macrophages with LPS doses ≤ 100 ng/ml. We found that P2X7 receptor increases the extracellular activity of TACE through the release of the mature form of TACE in exosomes. This effect was blocked using P2X7 receptor inhibitors or in macrophages obtained from P2X7 receptor-deficient mice. Elevation of intracellular Ca2+ and p38 mitogen-activated protein kinase after P2X7 receptor activation were involved in the release of TACE, which was able to process TNF-alpha on nearby expressing cells. Finally, we observed an increase of TNF-alpha in the peritoneal lavage of mice treated with LPS and ATP. In conclusion, P2X7 receptor induces the release of TACE in exosomes to the extracellular compartment that could amplify the pro-inflammatory signal associated to this receptor. These results are important for the development of therapeutics targeting P2X7 receptor.